New ready mix formulation of chlorantraniliprole plus lambda cyhalothrin with translaminar action against insect pests of soybean - Kambrekar, D N (Indian Journal of Plant Protection, 2020)
The use of foliar insecticides has historically been a common and effective management strategy for lepidopteran pests in soybean, Glycine max (L.). A novel insecticide in the anthranilic diamide and a pyrethroid class, AMPLIGO (Chlorantraniliprole 9.3% w/w + Lambda cyhalothrin 4.6% w/w) was demonstrated significant levels of toxicity to several lepidopteron insect pests worldwide in the recent past. The main objective of this study was to evaluate the toxicity of new ready mix formulation of Chlorantraniliprole + lambda cyhalothrin against insect pests of soybean during two seasons (2016 and 2017) in the Main Agricultural Research Station, University of Agricultural Sciences, Dharwad (KarnatakaIndia). The results revealed that applications of Chlorantraniliprole 9.3 %+ Lambda cyhalothrin 4.6% ZC @ 200 ml/ha was effective in reducing the various insect pest population in soybean viz., Spodoptera litura (Fab.), Thysanoplusia orichalcea (Fab.) and Obereopsis brevis (Swed). Chlorantraniliprole 9.3 %+ lambda cyhalothrin 4.6% ZC @ 200 ml/ha recorded lowest population of semilooper with 0.67 and 0.97 larvae per meter row length during 2016 and 2017 respectively. Similarly, the same dosage has recorded lowest larval population of Spodoptera litura (0.67 and 1.00 larvae per meter row length) and girdle beetle (0.67 and 0.33 damaged plants per meter row length) during both the years of investigations. Further, chlorantraniliprole 9.3 %+ lambda cyhalothrin 4.6% ZC @ 200 ml/ha recorded highest yield of 17.57 and 18.68 q/ha respectively during the first and second year of experimentation.